SURVEI SARANA DAN PRASARANA OLAHRAGA SEKOLAH MENENGAH PERTAMA DIKECAMATAN TUNGKAL ILIR KABUPATEN TANJUNG JABUNG BARAT - Wijaya, Dian Candra; Palmizal A, Palmizal A; Muzaffar, Ahmad (STKIP Melawi, 2025)
Abstract: The purpose of this study was to determine the condition and completeness of sports facilities and infrastructure in Junior High Schools in Tungkal Ilir District with the hope that sports facilities and infrastructure can support physical education learning, and help students to hone their potential through sports activities. The research method uses a quantitative descriptive design using an observation sheet as a research instrument to record the existence and condition of sports facilities and infrastructure in Junior High Schools in Tungkal Ilir District based on the Regulation of the Minister of National Education No. 24 of 2007. The population in the study included 6 State/Private Junior High Schools in Tungkal Ilir District. Based on the results of the study, the existence and condition of sports facilities and infrastructure in Junior High Schools in Tungkal Ilir District showed 65%